The Ethos of the Historian: The Minutes of Evidence Project, and Lives Lived with Law on the Ground - Julie Evans (Law Text Culture, 2016)
I sit writing this from Lewes, a town that nestles by the chalky edge of the Downs in Southeast England. I have come here to spend some sabbatical leave at the University of Sussex, with colleagues and friends, historians like me. We have been working together for several years on a project called Minutes of Evidence, in which we have tried to make sense of the myriad ways in which settler colonialism operated, as a matter of law and administration, across the British Empire and within individual colonies, and to consider its impacts on everyday lives and questions of justice, past and present.